Understanding the mechanisms of food effect on omaveloxolone pharmacokinetics through physiologically based biopharmaceutics modeling - Xavier J. H. Pepin; Scott M. Hynes; Hamim Zahir; Deborah Walker; Lois Q. Semmens; Sandra Suarez‐Sharp (Wiley, 2024)
Abstract Omaveloxolone is a nuclear factor (erythroid‐derived 2)‐like 2 activator approved in the United States and the European Union for the treatment of patients with Friedreich ataxia aged ≥16 years, with a recommended dosage of 150 mg orally once daily on an empty stomach. The effect of the US Food and Drug Administration (FDA) high‐fat breakfast on the pharmacokinetic profile of omaveloxolone observed in study 408‐C‐1703 (NCT03664453) deviated from the usual linear correlation between fed/fasted maximum plasma concentration (Cmax) and area under the concentration-time curve (AUC) ratios reported for various oral drugs across 323 food effect studies. Here, physiologically based biopharmaceutics modeling (PBBM) was implemented to predict and explain the effect of the FDA high‐fat breakfast on a 150‐mg dose of omaveloxolone. The model was developed and validated based on dissolution and pharmacokinetic data available across dose‐ranging, food effect, and drug-drug interaction clinical studies. PBBM predictions support clinical observations of the unique effect of a high‐fat meal on omaveloxolone pharmacokinetic profile, in which the Cmax increased by 350% with only a 15% increase in the AUC. Key parameters influencing omaveloxolone pharmacokinetics in the fasted state based on a parameter sensitivity analysis included bile salt solubilization, CYP3A4 activity, drug substance particle size distribution, and permeability. Mechanistically, in vivo omaveloxolone absorption was solubility and dissolution rate limited. However, in the fed state, higher bile salt solubilization led to more rapid dissolution with predominant absorption in the upper gastrointestinal tract, resulting in increased susceptibility to first‐pass gut extraction; this accounts for the lack of correlation between Cmax and AUC for omaveloxolone.